2011
DOI: 10.1103/physrevb.83.235305
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ordered arrangements of cluster chains on the hopping transport in GaAs:Mn/MnAs hybrids at low temperatures

Abstract: Two different arrangements of cluster chains consisting of elongated MnAs nanoclusters were deposited on (111)B-GaAs substrates by selective-area metal-organic vapor-phase epitaxy. This method allows one a controlled positioning of the nanoclusters on the substrate, offering the possibility to investigate the influence of the nanocluster arrangement on the transport properties of granular hybrid structures. Magnetotransport measurements at low temperatures were performed for both cluster-chain arrangements pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…The magnetic properties, such as the magnetotransport and MR effects, of the NC arrays were tuned by controlling the size, shape, and arrangement of the ferromagnetic MnAs NCs on the semiconducting substrates using our SA‐MOVPE techniques , and by specially designing the MR device structures . In addition, we proposed magnetic sensor devices that were based on the ordered planar arrangements of the connected MnAs NCs in accordance with the theoretical calculation results .…”
Section: Introductionmentioning
confidence: 66%
“…The magnetic properties, such as the magnetotransport and MR effects, of the NC arrays were tuned by controlling the size, shape, and arrangement of the ferromagnetic MnAs NCs on the semiconducting substrates using our SA‐MOVPE techniques , and by specially designing the MR device structures . In addition, we proposed magnetic sensor devices that were based on the ordered planar arrangements of the connected MnAs NCs in accordance with the theoretical calculation results .…”
Section: Introductionmentioning
confidence: 66%
“…The SA-MOVPE is promising as it enables us to accurately adjust the size, shape, number, position, and spatial arrangement of the MnAs NCs [16][17][18][19] within the hybrids to tune its magnetic and magnetotransport properties. 3,[20][21][22] Ordered planar arrangements of coupled NCs show large MR effects 23 and MR ratios of 300% are predicted by theory. 24 However, it was observed that Mn provided during the NC growth diffused into the undoped semiconducting layers, in which it was incorporated as an acceptor yielding a p-type conductive diluted magnetic semiconducting layer.…”
mentioning
confidence: 97%
“…Growth of high-quality MnAs nanoclusters by selective-area metal-organic vapor-phase epitaxy (SA-MOVPE) offers a number of advantages in the design of lateral magnetoelectronic device structures as degrees of freedom such as size, shape, and position can easily be * matthias.elm@exp1.physik.uni-giessen.de tuned and controlled [21][22][23]. Recently, a spin-valve-like behavior was reported for an arrangement of two MnAs nanoclusters [20,24].…”
Section: Introductionmentioning
confidence: 99%